Experimental study on mechanical properties and damage mechanism of basalt fiber reinforced concrete under uniaxial compression. (June 2021) - Yang, Liyun; Xie, Huanzhen; Fang, Shizheng; Huang, Chen; Yang, Aiyun; Chao, Yuh J.
Abstract: In this study, the effects of basalt fiber content on the uniaxial compressive mechanical properties and damage of concrete were investigated. Acoustic emission (AE) technology was adopted to collect the AE characteristic parameters (ringing count and energy) in the entire loading process, and the change trend of the characteristic parameters from initial compression to final complete failure was analyzed during the uniaxial compression test of basalt fiber-reinforced concrete (BFRC). 3D-digital image correlation was used to record the surface strain field and track the surface crack development in real time. Research results show that a proper amount of basalt fiber (6 kg/m 3 ) can improve the compressive strength of concrete and reduce the density and intensity of AE characteristic parameters. The change in AE characteristic parameters is closely related to the stress–strain curve of BFRC and includes three stages, namely, initial compaction, stable crack propagation, and unstable crack propagation stages. With the increase in basalt fiber content, AE events are dispersed in concrete, effectively weakening the local damage. The strain contours show that adding a proper amount of basalt fiber can delay the early cracking and reduce the transverse strain of concrete. At the same time, the long cracks on the surface of BFRC gradually transform into many microcracks with the increase in basalt fiber content.